2017
DOI: 10.1515/eko-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Disturbances on Odonata Assemblages along a Tropical Polluted River

Abstract: Abdul N.H., Rawi Che S.Md., Ahmad A.H., Al-Shami S.A.: Effect of environmental disturbances on Odonata assemblages along a tropical polluted river. Ekológia (Bratislava), Vol. 36, No. 4, p. 388-402, 2017. Odonata larvae have been intensively used as bioindicators for freshwater pollution as their community structure closely follow changes in the environment and habitat settings. In this study, 28 taxa of Odonata larvae were collected from three stations (upper, middle and lower) of a polluted river in Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
1
6
0
4
Order By: Relevance
“…This finding reinforces the importance of maintaining man-made waterbodies for conservation outcomes in oil palm production landscapes (Sulai et al, 2015). Our data are comparable with Abdul et al (2017) who recorded 22 Odonate species at larval stage, collected from a river which passes through an oil palm plantation in the northern part of Peninsular Malaysia. However, our study suggested that Odonata communities supported by oil palm waterways are impoverished in comparison to natural forests.…”
Section: Discussionsupporting
confidence: 89%
“…This finding reinforces the importance of maintaining man-made waterbodies for conservation outcomes in oil palm production landscapes (Sulai et al, 2015). Our data are comparable with Abdul et al (2017) who recorded 22 Odonate species at larval stage, collected from a river which passes through an oil palm plantation in the northern part of Peninsular Malaysia. However, our study suggested that Odonata communities supported by oil palm waterways are impoverished in comparison to natural forests.…”
Section: Discussionsupporting
confidence: 89%
“…Also, this is an indication of the considerable adaptive capabilities of dragonflies in relation to the cyclic disturbances that their populations may be exposed to. Abdul et al (2017) have drawn attention to this aspect in studies of dragonfly assemblages of a polluted river: dragonflies developed many morphological and physiological adaptations in order to counter the deterioration in habitat quality.…”
Section: Discussionmentioning
confidence: 99%
“…of Odonata was recorded at SR5. Taxa of Odonata tend to inhabit the sediment and between rocks or leaves, and they are associated with macrophytes (Abdul et al 2017). Meanwhile, Erpobdella sp.…”
Section: Benthic Macroinvertebrates and Environmental Variablesmentioning
confidence: 99%